(untitled) (Annual of the Faculty of Philosophy in Skopje, 2007)
In the last few years crisis managing has become a priority theme for the security agenda of international governmental and non governmental organizations. Previously; crisis management was a priority between the contenders of the cold war, today, this theme results from new security challenges of non classic threats. As legitimate question and prerequisite for successful security realization, crisis managing has also become a part of the agenda of many western democracies, democracies in transition and post conflict societies. Hence, Crisis Management has become a part of post conflict Macedonian agenda. More serious urges for crisis management perspectives in Republic of Macedonia have arisen as conceptual answer for several reasons: - new security surrounding and challenges; - leaving of traditional defense; - effective and in time handle with risks and modern world threats system; - having no regulations or practice of coordinating the crisis assessment; - there is need of security system institution being in charge of crisis prevention and crisis handling.